(untitled) (World Bulletin of Public Health, 2024)
This article explores the importance of using a multidisciplinary approach to the management of concomitant urological pathology in patients with prostate cancer. It discusses the relationship between prostate cancer and urological conditions, provides a literature review, suggests effective methods of integrated care, and provides insight into potential outcomes and debates. Ultimately, it highlights the importance of collaboration between healthcare professionals to optimise patient outcomes.